MODEL PEMBUDAYAAN KARAKTER KEAGAMAAN MELALUI KEGIATAN EKSTRAKURIKULER DI SMPN1 MAKALE TANA TORAJA - Mujizatullah Mujizatullah (Balai Penelitian dan Pengembangan Agama Makassar, 2017)
This study aims to determine the implementation of religious character educationthrough Religious Extracurricular in State Junior High School 1 Makale by using adescriptive explorative approach qualitative. Data collection techniques used in thisstudy interview, observation, study documents. Research results cultural charactermodel through Religious Extracurricular activities has been implemented in severalactivities such as Rohis, Pesantren Kilat, Tadarrus, Fasting, open and sahur togetherand supported by the implementation multicultural education is high enough that thetolerance between religious communities is quite good, but the constraining factor isstill limited educators in the field of religion